Matemática e libras: dos meus desafios aos desafios indicados em pesquisas entre 2018 e 2022 - Jordão, Maria Maisa Farias (2023)
Deaf Education and Mathematics teaching involves the understanding of several languages in addition to calculations. Thus, the theme of this dissertation arose as a result of my own experience as a deaf woman, student, teacher and researcher in the field of education, where it was possible to verify the difficulties in relation to the process of teaching and learning mathematics for deaf students. Initially, this study aimed to analyze the teaching and learning process for deaf students in the 9th year of elementary school, within the scope of Mathematics, in a school for the deaf in Fortaleza-CE, verifying the strategies, challenges and possibilities that the teaching environment of Mathematics can present and, consequently, what it can provide to its actors in the Final Years of Elementary School, hearing teachers and deaf learners. However, given the difficulties caused during the Covid-19 pandemic period, I decided to carry out a bibliographical research on academic works (including dissertations and theses) that covered the teaching of bilingual mathematics. Part of the reference covers a little of my life story and my experience with mathematics. In fact, according to Monteiro (2018), there were 148 deaf people among masters and doctors with academic training in Brazil. However, when analyzing each person's lattes, none of them explicitly included research or studies in Mathematics. This time, I emphasize the importance of presenting my life story. This research has the following question: What scientific knowledge related to the teaching of mathematics to deaf students is present in theses and dissertations and comprised between the time period of 2018 and 2022, including bilingual teaching and/or participation of deaf teachers? The aim is to analyze the contributions of the work produced, investigating the educational levels in its scope and what actions are proposed in teaching deaf students, whether there is a standard in the pedagogical strategies with this audience, making learning viable. Works involving educational products, teacher training and case studies with hearing teachers were excluded. My purpose is to investigate the scientific production on the exposed topic, clarifying proposals for teaching mathematics to the deaf, categorizing which teaching stages, which contents and which teaching strategies are being used and researched for learning for this audience. I found 11 works, two theses and eight dissertations, satisfying my “longin”.